Does Teacher Testing Raise Teacher Quality? : Evidence from State Certification Requirements - Joshua D. Angrist; Jonathan Guryan (Institute for the Study of Labor (IZA), 2005)
The education reform movement includes efforts to raise teacher quality through stricter certification and licensing provisions. Most US states now require public school teachers to pass a standardized test such as the Praxis. Although any barrier to entry is likely to raise wages in the affected occupation, the theoretical effects of such requirements on teacher quality are ambiguous. Teacher testing places a floor on whatever skills are measured by the required test, but testing is also costly for applicants. These costs shift teacher supply to the left and may be especially likely to deter high-quality applicants from teaching in public schools. Moreover, test requirements may disqualify some applicants that schools would otherwise want to hire. We use the Schools and Staffing Survey to estimate the effect of state teacher testing requirements on teacher wages and teacher quality as measured by educational background. The results suggest that state-mandated teacher testing increases teacher wages with no corresponding increase in quality.
Keywords: J45; J44; I28; 330; occupational licensure; education reform; worker screening; Lehrkräfte; Weiterbildung; Qualifikation; Berufsbildungspolitik; Schätzung; Vereinigte Staaten